Teacher attitudes, cultural beliefs, and problems experienced teaching children with disabilities in Nigeria - Obisesan, Oluseun (2020)
There are more people with disability in developing countries than in other parts of the world.Cultural beliefs or local narratives in these parts of the world explain disability and how people relate to them.The purpose of this study is to see how teachers’ background factors,cultural beliefs and problem experienced teaching students with disability affect teacher’s attitude. For the study, data was obtained from 356 respondents.The data was collected through convenience sampling method from in-service teachers ( primary and secondary school) working in both public and private secondary schools in South Western part of Nigerian. The result shows that teacher’s gender,educational background, and Kind of school are demographic variables that affect attitude.Cultural beliefs were also found to affect attitudes in this study.Problems teachers faced did not affect their attitude. The study concludes that continued effort by the government in improving teacher education programs and support of public schools is important.